24 Frames 24 Hours. Issue 1 (1st October 2013) - Schleser, Max R. C.; Turnidge, Tim
24 Frames 24 Hours defines mobile film-making in a cultural context. The study draws on new paradigms of participation and simultaneously analyses creative processes while developing connections in the local community in a global perspective. Besides the aesthetic refinement of mobile film-making, the research project is a prototype for community involvement through creative practices. Local communities engage in mobile film-making and shape representations about their communities and futures. Through a custom-design, user-interface with GPS functionality, mobile videos will be linked into a global collaborative documentary project. Innovation will manifest itself in leveraging into twenty-first-century creativity and new forms of self-expression.